An Analysis of the Status of Urban Development Indicators with a Spatial Justice Approach, Case Study: Ilam city - Fatemeh Mirzabeigi; Hossein Mojtaba Zadeh; Rahim sarvar (تحقیقات کاربردی علوم جغرافیایی)
by examining the level of inequality in the distribution of services and identifying the spatial pattern of injustice in the city, we can find out which of the services are in a more unfavorable situation than in this way, city management with conscious performance in spatial distribution of public services and social interests. , Reduce spatial inequalities and improve the quality of life and ensure sustainable urban development. The present research is applied and its research method is descriptive-analytical. The purpose of this analytical research is on the status of Ilam urban development indicators in order to achieve spatial justice, which uses the capabilities and facilities of geographic information system, including: map composition, Spatial statistics, etc. have been done. The results show that the spatial distribution of services in Ilam city is not desirable and the results of this study show that the concentration of urban facilities and services has occurred in the central part of the city and other areas are low in terms of urban resources and facilities. The research findings show that 20% of the city's population lives in relatively affected areas and 23.2% in areas with semi-sustainable development, and over 50% of residents live in deprived and completely deprived areas in terms of development in Ilam city. The results of the Vikor model are not considered to be sustainable development in any area. However, based on the results of the research, the focus of urban services in Ilam city follows the center-perimeter model, which means that everything from the central areas to We move around the area, reducing the distribution of services.